2014
DOI: 10.1179/1743289814y.0000000092
|View full text |Cite
|
Sign up to set email alerts
|

α,ω-Alkanedithiol cross-linking of high vinyl 3,4-polyisoprene

Abstract: This paper evaluates the ability of a,v-alkanedithiols to cross-link high vinyl 3,4-polyisoprene rubber (represented by Isogrip) through the thiol-ene addition reaction and provides microstructural insights into where cross-linking takes place. The thiol-ene reactions are the hydrothiolation of a C5C bond, which can be initiated in a number of ways. It has been postulated that organic peroxides are very effective in initiating such cross-links and that a,v-alkanedithiolene cross-linking of high vinyl 3,4-polyi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
(70 reference statements)
1
1
0
Order By: Relevance
“…However, attenuated total reflection (ATR) and high resolution solid state carbon nuclear magnetic ressonance ( 13 C NMR) analyses showed that in this case the 1,2-vinyl isoprene were minimally affected after the thiol-ene addition process when compared to the more substituted double bonds. [166] Similar results were also observed by Ertem et al [167] Interestingly, these observations suggest that hydrothiolation occur preferentially on double bonds which led to more stable radical intermediates. For example, at the 3,4-allyl units the abstraction of a hydrogen atom from the methyl group to can afford an ally radical intermediate, while the in-chain double bonds form tertiary radical intermediates.…”
Section: Rubber Modifications Via Thiol-x Reactionssupporting
confidence: 75%
“…However, attenuated total reflection (ATR) and high resolution solid state carbon nuclear magnetic ressonance ( 13 C NMR) analyses showed that in this case the 1,2-vinyl isoprene were minimally affected after the thiol-ene addition process when compared to the more substituted double bonds. [166] Similar results were also observed by Ertem et al [167] Interestingly, these observations suggest that hydrothiolation occur preferentially on double bonds which led to more stable radical intermediates. For example, at the 3,4-allyl units the abstraction of a hydrogen atom from the methyl group to can afford an ally radical intermediate, while the in-chain double bonds form tertiary radical intermediates.…”
Section: Rubber Modifications Via Thiol-x Reactionssupporting
confidence: 75%
“…19 Thiol-ene chemistry has been used as a powerful tool to develop new polymer materials, where new properties are achieved depending on the nal applications needs. In particular, it has been used in order to introduce alternative ways of crosslinking, [20][21][22][23][24][25][26][27][28][29][30][31][32][33] for reversible cross-linking, 34,35 for selfhealing purposes, [36][37][38][39] for surface functionalisation [40][41][42][43][44][45][46][47][48][49] and enhance blend compatibility, [50][51][52][53][54][55] on double bond containing elastomers such as Natural Rubber (NR), Synthetic Polyisoprene (IR), Polybutadiene Rubber (BR), Nitrile Rubber (NBR), Styrene-Butadiene Rubber (SBR) and Ethylene Propylene Diene Monomer Rubber (EPDM). More recently, thiol-ene reaction was found to be effective also on low reactivity elastomers, such as Polychloroprene Rubber (CR), to develop a recyclable and self-healable material.…”
Section: Introductionmentioning
confidence: 99%